Impacts of hospital wait time on patient health and labor supply - Anna Godøy; Venke Furre Haaland; Ingrid Huitfeldt; Mark Votruba (Statistics Norway, Research Department, 2019)
We estimate the effects of wait time for orthopedic surgery on health and labor market outcomes of Norwegian workers. Our identification strategy exploits variation in wait times for surgery generated by the idiosyncratic variation in system congestion at the time of referral. While we find no significant evidence of lasting health effects, longer wait times have persistent negative effects on subsequent labor supply. For every 10 days spent waiting for surgery, we estimate health-related workplace absences increase 8.7 days over the five years following referral, and the likelihood of permanent disability insurance increases by 0.4 percentage point. Cost benefit calculations point to sizable fiscal savings from shorter wait times.
Keywords: I12; J32; 330; Wait time; queues; hospital treatment; health outcomes; labor market attachment; sickness absence